Youth Leadership Development in the Start2Finish Running & Reading Club - Shaikh, Majidullah; Bean, Corliss; Forneris, Tanya (Université d'Ottawa | University of Ottawa, 2019)
Researchers have asserted that offering intentional leadership roles to youth can help them to develop life skills (e.g., communication, decision-making); however, few physical-activity-based positive youth development programs provide youth these intentional leadership roles, and little research has explored the impact of these opportunities on youth who take them up. The purpose of this study was to understand the developmental experiences of youth leaders in a physical-activity-based positive youth development program. Sixteen youth leaders (Mage= 13.37, SD = 1.36) from 4 sites of the Start2Finish Running & Reading Club participated in semi-structured interviews to discuss their experiences as junior coaches. Fertman and van Linden’s (1999) model of youth leadership development was used to guide the data collection and analysis. Through deductive-inductive thematic analysis, 3 themes were constructed: (a) awareness: developing into leaders started with seeing potential through role models, (b) interaction: learning by doing and interacting with others helped youth to practice leadership abilities, and (c) mastery: taking on greater responsibility allowed for opportunities to refine leadership abilities and develop a variety of life skills. These themes helped to bring an understanding to the processes involved in leadership and life-skill development. Practical and research implications are discussed regarding leveraging youth leadership opportunities in youth programming.